Komunikasi Pemasaran Sosial pada Program Keluarga Berencana - Fa'iq Ar Rozzaq; Yulianti (UNISBA Press, 2024)
Abstract. Rapid population growth in Indonesia is a major concern, affecting various aspects of life from economic to social. This research aims to find out the important role of Family Planning (KB) in dealing with the impact of population growth through social marketing strategies. The research methodology in this research is quantitative research. Quantitative research is research whose findings can be applied generally because they describe or explain a problem. The type of research in this study uses quantitative methods with descriptive study analysis. The use of descriptive studies in this research focuses on social marketing in family planning programs which include the 7P model (Seimour, 1990): producer, purchaser, price, promotion, place, probing, and products in the family planning program in RW 04 Rancameong. Researchers used data collection techniques, including: interviews and observations chosen in this study by looking for data information on respondents. The research results show that in the producer aspect BKKBN RW 04 Rancameong acts as a trained information spokesperson, in the purchaser aspect of prospective brides, mothers, mothers giving birth, and teenagers as social marketing targets, in the product aspect there is a maternal child health program, and a family planning program which is the program, in the price aspect there is time, effort and lifestyle changes for the people of RW 04 Rancameong, in the promotion aspect there is a door to door marketing strategy, and marketing via social media, in the place aspect BKKBN collaborates with the RW 04 Rancameong health center, and in the probing aspect there is a concept regarding the family planning program that will be carried out by BKKBN RW 04 Rancameong through a weekly program and a monthly program. Abstrak. Pertumbuhan penduduk yang pesat di Indonesia menjadi perhatian utama, mempengaruhi berbagai aspek kehidupan dari ekonomi hingga sosial. Penelitian ini bertujuan untuk mengetahui bagaimana peran penting Keluarga Berencana (KB) dalam menangani dampak pertumbuhan penduduk melalui strategi pemasaran sosial. Metodologi penelitian dalam penelitian ini ialah penelitian kuantitatif. Penelitian kuantitatif adalah penelitian yang hasil temuannya dapat diterapkan secara umum karena menggambarkan atau menjelaskan suatu persoalan. Jenis penelitian pada penelitian ini menggunakan metode kuantitatif dengan analisis studi deskriptif. Penggunaan studi deskriptif pada penelitian ini pada memfokuskan pemasaran sosial pada program keluarga berencana yang meliputi, model 7P, (Seimour, 1990) : producer, purchaser, price, promotion, place, probing, dan product pada program keluarga berencana di RW 04 Rancameong. peneliti menggunakan teknik pengumpulan data, di antaranya: wawancara, dan observasi yang dipilih pada penelitian ini dengan mencari informasi data terhadap responden. Hasil penelitian menunjukan bahwa dalam aspek producer BKKBN RW 04 Rancameong berperan sebagai juru bicara informasi yang terlatih, dalam aspek purchaser calon pengantin, pus, ibu melahirkan, dan remaja sebagai target pemasaran sosial, dalam aspek product terdapat program kesehatan ibu anak, dan program keluarga berencana yang menjadi programnya, dalam aspek price terdapat waktu, usaha, dan perubahan gaya hidup bagi masyarakat RW 04 Rancameong, dalam aspek promotion terdapat strategi pemasaran door to door, dan pemasaran melalui media sosial, dalam aspek place BKKBN bekerja sama dengan puskesmas RW 04 Rancameong, dan dalam aspek probing terdapat konsep mengenai program KB yang akan dilakukan BKKBN RW 04 Rancameong melewati program mingguan, dan program bulanan.